Evaluating innovation capabilities of real estate firms: a combined fuzzy Delphi and DEMATEL approach - Kumar, Anil; Kaviani, Mohamad Amin; Hafezalkotob, Ashkan; Zavadskas, Edmundas Kazimieras (International Journal of Strategic Property Management, 2017)
Due to strong competition, numerous technology advancements and the monetary policy of the government, the survival of Indian real estate firms now depends on their capacity to measure their existing innovation capabilities, rebuild them and adopt new ones. The aim of this study is to evaluate the technology and human resources innovation capabilities of Indian real estate firms by applying fuzzy Delphi and DEMATEL techniques. After identifying the innovation capabilities through an extensive literature review, a questionnaire is designed based on fuzzy linguistic scales to manage any vagueness of information received. Data has been collected from experts in the field, with capabilities then finalized by using a fuzzy Delphi method. To establish cause-effect relationships among capabilities, a DEMATEL method is applied to the data collected from a second questionnaire. Analysis of the data divides capabilities into two groups i.e. cause and effect. The results show that innovation management, robustness of product and process design capability, strategic planning and knowledge resources fall in the cause group; these are critical findings given the effect on the other capabilities. The study outcomes can help real estate firms to enhance their capabilities with the proposed model providing guidelines and direction in this regard.